2019
DOI: 10.7150/thno.35988
|View full text |Cite
|
Sign up to set email alerts
|

Acetyl-11-keto-β-boswellic acid attenuates titanium particle-induced osteogenic inhibition via activation of the GSK-3β/β-catenin signaling pathway

Abstract: Rationale: Peri-prosthetic osteolysis (PPO) is mainly induced by wear particles and represents the leading cause of implant failure and revision surgery. Previous studies have identified mitigation of wear particle-induced inflammation and bone resorption as the main approaches to treat PPO. Recently, wear particle-induced reduction of bone formation around the prosthesis was identified as a major factor in the development of PPO. Acetyl-11-keto-β-boswellic acid (AKBA), a derivative of frankincense, has been s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 62 publications
3
23
0
Order By: Relevance
“…40 Therefore, potential molecular mechanisms were investigated by examining the expression of key markers, such as β-catenin and p-GSK-3β, which might be involved in the relevant signaling pathways during the osteogenic differentiation of MC3T3-E1 cells. 41,42 As expected, WB analysis demonstrated that the level of β-catenin and p-GSK-3β was increased in Cit-NRIII-treated cells (Figure 5I-K), indicating that the Wnt/β-catenin signaling pathway might play a major role in citrate-stabilized AuNRs-induced osteogenic differentiation in MC3T3-E1 cells.…”
supporting
confidence: 71%
“…40 Therefore, potential molecular mechanisms were investigated by examining the expression of key markers, such as β-catenin and p-GSK-3β, which might be involved in the relevant signaling pathways during the osteogenic differentiation of MC3T3-E1 cells. 41,42 As expected, WB analysis demonstrated that the level of β-catenin and p-GSK-3β was increased in Cit-NRIII-treated cells (Figure 5I-K), indicating that the Wnt/β-catenin signaling pathway might play a major role in citrate-stabilized AuNRs-induced osteogenic differentiation in MC3T3-E1 cells.…”
supporting
confidence: 71%
“…Orally administered AKBA exerts anti-arthritic activity in bovine serum albumin-induced arthritis. Additionally, AKBA inhibits the toll-like receptor-mediated activation of monocytes through the downregulation of LPS-induced nitric oxide, IL-β, and TNF-α production [ 18 , 19 , 20 , 21 ]. Therefore, this study used βBA to develop a therapeutic agent against bone diseases, which has higher absorption efficiency in vivo than AKBA, may be effective as a drug.…”
Section: Discussionmentioning
confidence: 99%
“…There are more than 12 types of BAs of which α-boswellic acid (αBA), β-boswellic acid (βBA), keto β-boswellic acid (KBA), and acetyl-keto β-boswellic acid (AKBA) are the major ones [ 19 ]. Previous studies reported that AKBA inhibits osteoclastogenesis by suppressing the NF-κB-induced TNF-α signaling pathway [ 20 ] and attenuates titanium particle-induced osteogenic inhibition via the GSK-3β/β-catenin signaling pathway [ 21 ]. However, the biological effects of βBA on osteoclast differentiation and bone resorption remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The optical density of experimental samples was detected at 450 nm using a microplate-reader (BioTek, Winooski VT, USA) and cell viability was studied. In addition, the cell growth inhibition rate which reflects the extent to which the cell proliferation ability is inhibited compared to the control was converted based on the CCK-8 data (31). In detail, the calculation formula is [growth inhibition rate = (1 − A450 nm value of the drug group/A450 nm value of the control group) × 100%].…”
Section: Cell Viability Assaymentioning
confidence: 99%